Synthesis of bis-azobenzene derivatives with reactive bromohexyl unit and carboxylic acid group based on Disperse Yellow 7 - Darabut, Alina Madalina; Purikova, Olha Hennadiivna; Lobko, Yevheniia Volodymyrivna (European Journal of Chemistry, 2020)
In this work, two types of azobenzene derivatives based on Disperse Yellow 7 (DY7, 4-[4-(phenylazo)phenylazo]-o-cresol) were synthesized, which are bis-azobenzenes bearing flexible functional 6-bromohexyl chain or carboxylic acid moiety. The first one was synthesized by alkylation of DY7 with an excess of 1,6-dibromohexane in the presence of a mild base (K2CO3). The second one (azo dye with carboxylic acid functionality) was obtained by the alkaline hydrolysis of the ester bond of the newly obtained DY7 derivative with the ethoxycarbonyl group. The synthesized compounds were characterized by different spectral analytical techniques such as 1H NMR, 13C NMR, FT-IR, and UV-Vis. They can be employed for the synthesis of a wide variety of azo-based materials, which may be suitable for photochromic systems and molecular electronics applications.